Kajian Pembuatan Kelapa Parut Kering (Desiccated Coconut) Di PT. Rejeki Bersamah, Kabupaten Simeulue - Suci Rahmi; Safrizal Safrizal; Yusmanizar Yusmanizar; Desi Susanti (Universitas Teuku Umar, 2021)
Dessicated coconut is a product that is processed from the flesh of old and fresh coconuts without the epidermis. The manufacture of dry grated coconut, there are several stages including the removal of coir, coconut shell, release of testa, washing, boiling, grating, drying, sifting, and packaging. The method used in this research is a study of processing processes, calculation of mass balance flow, yield, and measurement of the moisture content of dry grated coconut. Processing of dry grated coconut using coconut as raw material as much as 15,000 Kg/process at PT. Rejeki Bersamah The dry grated coconut produced is 2000 kg/process. The average yield of dry grated coconut produced ranged from 46-100% with an overall average yield of 13.3%. The water content of each processing of dry grated coconut produced by PT. Rejeki Bersamah, the average ranged from 1.3% - 69.66 %. The water content obtained from dry grated coconut at PT. Rejeki Bersamah of 1.3%. This percentage indicates that dry grated coconut meets quality standards.Keywords: Dry Grated Coconut, Mass Balance, Moisture Content, PT. Rejeki Bersamah.